Designing fake nail product packaging at MSME dairy nails using the Quality Function Deployment (QFD) method - Dwiariani, Rafifah; Praptono, Budi; Yastica, Tiara Verita (Universitas Mercu Buana, 2025)
Dairy Nails is one of the MSMEs that provides quality artificial nail products in Bandung with various designs. In a survey conducted of Dairy Nails customers, there was a decrease in buying interest caused by customer dissatisfaction. One of the reasons for this is the false nail packaging that does not meet customer expectations. Packaging is an important factor in a product because it protects the product inside. Therefore, it is necessary to improve the packaging design of artificial nails that can increase consumer buying interest. Proposed improvements will be made using the Quality Function Deployment (QFD) method, which makes consumer needs a reference in product design. Thus, the proposed packaging design can meet consumer desires and expectations. The results of this study are designing false nail packaging according to customer wants and needs with specifications, namely polycarbonate plastic material, with a clamshell packaging shape, using a hinged lid method cover, with a font size of 12 pt; the font types used are Arapey and Moontime, and the proposed beige packaging has a logo and has dimensions of 8.5 x 8.5 cm. Thus, the packaging contributes to better showing the product, is informative, and can be reused by consumers.